SOILS DEVELOPED ON SERPENTINITE IN PANYIPATAN DISTRICT, SOUTH KALIMANTAN : CHARACTERISTICS AND THEIR SUITABILITY FOR MAIZE - YATNO, EDI; PRASETYO, BAMBANG HENDRO (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2010)
Four representative soil pedons formed from ultrabasic or serpentinite parent materials were studied in the field and laboratory in order to determine their soil characteristics and suitability for maize. Maize is one of the most important agricultural food crops in Indonesia. Up to now, the need of this crop for any other usages tends to increase. However, maizeproduction could not meet the demand. Therefore, extensification and intensification of the agricultural area for the crop cultivation need to be conducted. The results indicated that all the studied soils have deep solum, yellowish red to red colour, blocky structure, and friable to firm consistency. Particle-size distribution was dominated by clay fraction (73-88%). The soil bulk density and available water was relatively low (0.84-1.12 mg m-3 and 9-15%, respectively), while the total porosity was high (58-68%). Except pedon PN-35, some soils have acid reaction, medium C organic in the upper horizons, and low base saturation (<40%). The soil CEC and exchangeable Al were low (<12 and <1.3 cmolc kg-1, respectively). P retention of all the soils is high (60-87%). The soils were classified as Typic Hapludox, Anionic Acrudox, and Kandiudalfic Eutrudox. Most soils were moderately suitable (S2) for maize cultivation with nutrient retention (acidreaction, low CEC-clay and base saturation) and water availability (high wet months) as the main limiting factors. To increase soil productivity, application of agricultural lime, P fertilizers (rock phosphate) and organic matter were highly recommmended.